Analysis Of Academic Procrastination And Self-Control In Students Who Switch Academic Work To Other Activities - Tari Patunnisa (PT. Global Research Collaboration, 2026)
Academic procrastination is a prevalent issue among university students and may undermine learning effectiveness, psychological well-being, and academic performance. This study aimed to examine the relationship between self-control and academic procrastination among college students. A quantitative survey design was employed, involving 33 students as the sample. Data were collected using an Academic Procrastination Scale and a Self-Control Scale administered via questionnaire, and were analyzed using correlation and simple linear regression. The results indicated a very weak association between self-control and academic procrastination (R = 0.081; R² = 0.007). The regression model was not statistically significant (p = 0.654), and the partial test also showed no significant effect (t = −0.453 < t-table = 2.039). These findings suggest that self-control was not a significant predictor of academic procrastination in the sampled students, implying that other psychological, environmental, or situational factors may play a more dominant role in shaping procrastination behavior. In conclusion, interventions to reduce academic procrastination should not rely solely on strengthening self-control, but should also consider broader determinants that influence students’ task engagement and learning regulation.